Carbon pool and respiration of rhizosphere soils of different mangrove plant species in bangladesh sundarbans (Bangladesh Journal of Botany, 2024)
Bangladesh Sundarbans like other mangrove ecosystems are vital carbon reservoirs in the global carbon cycle. Soil respiration, a key carbon flux, is closely linked to climate change. Despite extensive research on the Sundarbans, a gap exists in studying rhizosphere soil carbon pool (SOC) and respiration (Rs), which is crucial for understanding its role in global climate dynamics, especially the local climate. This study investigated SOC pools and Rs rates of oligohaline, mesohaline, and polyhaline zones of the Bangladesh Sundarban Mangrove Forests (SMF). The oligohaline zone exhibited the highest average SOC content (11.26 ± 5.52 t/ha), followed by the mesohaline zone (9.91 ± 3.09 t/ha) and the polyhaline zone (9.86 ± 4.16 t/ha). The Rs rate was comparatively higher in the mesohaline zone (28.19 ± 5.02 mg CO2/g soil), followed by the polyhaline zone (27.81 ± 4.38 mg CO2/g soil), and the oligohaline zone (27.63 ± 4.16 mg CO2/g soil) though the differences were not significant. Further analyses explored the influences of plant species on SOC and Rs. While rhizosphere soil of distinct plant species displayed varying SOC values, Rs did not exhibit significant differences among different plant species, and no significant relation was observed between Rs and SOC values. Mangroves were noted to store substantial amounts of organic carbon in their soils, yet they released relatively less carbon dioxide (CO2) through soil respiration compared to other tropical forests. This unique characteristic underscores the critical role of mangroves in global climate change dynamics. Conclusively, this study offers insightful information about the carbon dynamics of the Bangladesh SMF, emphasizing the significance of mangroves as carbon reservoirs with the potential to influence climate change adaptation strategies.Bangladesh J. Bot. 53(1): 131-140, 2024 (March)